Left Ventricular Noncompaction Cardiomyopathy (LVNC) with Left Ventricular Apical Thrombus– A Case Study (Journal of Armed Forces Medical College, Bangladesh, 2017)
Left ventricular non-compaction (LVNC) is a rare congenital cardiomyopathy, with or without LV dysfunction, characterized by prominent trabeculations and associated deep recesses which communicate with the ventricular cavity rather than the coronary circulation. LVNC affects all age groups and can occur in isolation or association with other cardiac and systemic anomalies, especially with neuromuscular disorders. Patient may be asymptomatic or present with ventricular arrhythmias, thromboembolism, heart failure and sudden cardiac death. Echocardiography is the most common tool for diagnosis of LVNC. Contrast ventriculography, computed tomography (CT) and magnetic resonance imaging (MRI) are other useful diagnostic tools. Due to increasing awareness and improvement in imaging methods, LVNC is being diagnosed frequently in patients now a day.Journal of Armed Forces Medical College Bangladesh Vol.13(1) 2017: 128-130